Comparison of meat yield and physicochemical characteristics of indigenous chicken and duck - Rana, MB; Mollah, MBR; Habib, M; Hashem, MA; Azad, MAK; Ali, MS (Meat Research, 2023)
Three indigenous male chicken and 3 indigenous male duck were slaughtered to compare the meat yield and quality characteristics. After slaughter meat yield characteristics of breast, thigh, drumstick, wing, liver, heart, head, gizzard, neck etc. were compared against their live weight. After comparing the yield characteristics the breast, thigh and drumstick of all birds were stored at 4˚C to evaluated different quality characteristics at 24-hour postmortem. The following parameters were compared; proximate composition, pH, cooking loss, drip loss, water holding capacity and instrumental color (CIE L* a* b*). Findings revealed that dressing, thigh, drumstick, breast, gizzard, heart and shank weight percentage were significantly higher in indigenous chicken (p<0.05), while blood weight, feather weight and head weight were significantly higher in indigenous duck (p<0.05). Significantly higher crude protein was observed in indigenous chicken breast and thigh meat (p <0.05), while ash and ether extract were significantly higher in indigenous duck breast and thigh meat. Significantly higher pH was observed in chicken breast and thigh meat compare to duck breast and thigh (p<0.05). Cooking loss was higher in duck breast but lower in thigh meat compare to chicken breast and thigh meat. Significantly higher (p <0.05) water holding capacity was found in duck breast compare to chicken breast meat (p <0.05). At 2 hour of post mortem, lightness (L*) of breast and thigh meat did not show significant differences (p , but highly significant difference was found in drumstick meat of chicken and duck (p Redness (a*) was significantly higher in duck breast and drumstick meat and yellowness was higher in duck breast at 2 hour of post mortem compare to chicken. At 24 hour of post mortem no significant differences were found between chicken and duck breast, thigh and drumstick meat. The present study reveals that the dressing, breast, thigh and drumstick weight percentage, crude protein and pH were significantly higher in the indigenous chicken compare to duck, while ether extract, ash and redness (a*) values were significantly higher in duck compare to chicken.